Method for improving high-temperature performance of selective laser melting IN718Plus alloy and IN718Plus alloy
By controlling the cooling speed and specific thermal treatment steps after controlling the thermal treatment, regulate the γ 'phase tissue in the IN718PLUS alloy, solve the problem of low density and unsatisfactory performance in the alloy production process, and achieve higher high temperature mechanical performance and performance. High temperature stability.
Patent Information
- Application Number
- CN202411317639.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-09-20
AI Technical Summary
In the prior art, the production process of IN718Plus alloy has problems such as low density, many hole defects, and serious element segregation, which limits the use and development of alloys. The performance of the sedimentary alloy of the selected laser melting technology is lower than that of the forgings, which is suitable. It is difficult to effectively improve its defects due to heat treatment.
By controlling the cooling rate after heat treatment and regulating the structure of the unipolar and bipolar strengthening phases, the IN718Plus alloy is prepared using selective laser melting technology and subjected to homogenization treatment, solid solution treatment and cooling double aging treatment to achieve the regulation of the γ' phase.
It improves the high-temperature mechanical properties and high-temperature stability of IN718Plus alloy, achieves better high-temperature performance, and solves the problem of unsatisfactory alloy performance under traditional heat treatment methods.
Smart Images

Figure CN119328160A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of high-temperature alloy performance, and specifically to a processing method for improving the high-temperature performance of additively manufactured high-temperature alloys and a high-temperature alloy. Background Art
[0002] IN718Plus alloy is a polycrystalline nickel-based high-temperature alloy. As an improved alloy of the widely used IN718 alloy, its service temperature is increased from 650℃ to 704℃. At the same time, IN718Plus alloy is an improved alloy of IN718 alloy. By adding W and Co elements and changing the proportion of Al and Ti elements, the main strengthening phase is successfully transformed from IN718~γ” phase to IN718Plus~γ'. This also increases the service temperature of IN718Plus alloy by nearly 55℃ compared with IN718 alloy, retaining its excellent hot working properties, so it is widely used in aerospace and other fields.
[0003] γ' phase is an intermetallic compound with L12 face-centered cubic structure. This phase is the main strengthening phase of IN718Plus alloy. Its main components are Ni, Al, and Ti. Its chemical formula can be approximately expressed as Ni3(Al,Ti), and its morphology is spherical. The size of γ' phase in IN718Plus alloy is small, generally not exceeding 100nm. The fine and dispersed γ' phase makes IN718Plus alloy have extremely excellent high-temperature mechanical properties.
[0004] At present, the production process of IN718Plus alloy is still mainly based on casting and forging. Cast alloys often have disadvantages such as low density, many pore defects, and serious element segregation, which limit the use and development of the alloy; and although the performance of forged alloys is better than that of cast alloys, complex structures are difficult to mass produce, and there is a serious waste of raw materials. The above problems not only limit the use prospects of IN718Plus alloy, but also reduce its service performance.
[0005] At the same time, by controlling the various parameters of the selective laser melting technology, it is possible to control the organization and grain size and achieve mass production of complex parts. However, due to its unique forming method, the organization is relatively special, making the performance of the deposited alloy lower than that of forgings. Appropriate heat treatment will greatly improve its defects and achieve the control of organization and performance. At present, the selective laser melting IN718Plus alloy still uses the standard forging heat treatment method, but its performance is not ideal. Therefore, it is necessary to improve the heat treatment steps and methods on this basis to improve the performance and provide help and basis for future applications. Summary of the invention
[0006] The object of the present invention is to avoid the shortcomings of the prior art and provide a method for improving the high temperature performance of IN718Plus alloy and IN718Plus alloy, which realizes the regulation of the organization of unipolar and bipolar strengthening phases by controlling the cooling rate after heat treatment, and proves in a tensile test that an IN718Plus alloy with a bipolar γ' phase with better high temperature performance is obtained.
[0007] To achieve the above object, the technical solution adopted by the present invention is: a method for improving the high temperature performance of IN718Plus alloy by selective laser melting, comprising the following steps:
[0008] Step 1: Prepare IN718Plus alloy specimens using selective laser melting:
[0009] On the selective laser melting platform of BLT S210, the selective laser melting forming experiment was carried out on the IN718Plus alloy powder prepared by gas atomization method under the conditions of laser power 85-185W, scanning rate 300-1350mm / s, layer thickness 0.02-0.03mm, and overlap spacing 0.06-0.2mm to obtain the deposited IN718Plus alloy sample;
[0010] Step 2: Homogenization:
[0011] The deposited IN718Plus alloy sample is subjected to the first heat treatment at a furnace temperature of 1050-1150°C and a heat preservation period of 1-1.8h, and then water-cooled to room temperature at a rate of 1200-1400°C / s to obtain the homogenized IN718Plus alloy sample;
[0012] Step 3: Solution treatment:
[0013] The homogenized IN718Plus alloy sample was subjected to a second heat treatment at a furnace temperature of 960-980°C for 1-1.5 hours, and then water-cooled to room temperature at a rate of 1200-1400°C / s.
[0014] Step 4: Cooling and double aging treatment:
[0015] Under the condition of furnace temperature of 780-796°C, keep it warm for 8h-9h, then cool it to 696-712°C at a cooling rate of 56°C per minute, keep it warm for another 8h-9h, that is, complete the third heat treatment, and finally, air cool it to room temperature at a rate of 200-300°C / s;
[0016] That is, the high temperature performance improvement of the selective laser melted IN718Plus alloy is completed.
[0017] Furthermore, the step 3, solution treatment is as follows:
[0018] After the second heat treatment is completed, the material is air-cooled to room temperature at a rate of 200-300°C / s.
[0019] Furthermore, the particle size of the IN718Plus alloy powder in step 1 is 15 μm to 45 μm.
[0020] Furthermore, the density of the IN718Plus alloy sample in step 1 is 8.236 g / cm3, the relative density is 99.83%, and the columnar grain size in the IN718Plus alloy sample is 5 to 50 μm.
[0021] Furthermore, the grains in the IN718Plus alloy sample after the homogenization treatment in step 2 are equiaxed grains, and the grain size is 28 to 30 μm.
[0022] Furthermore, in the step 3, the IN718Plus alloy sample after homogenization is subjected to a second heat treatment at a furnace temperature of 960° C. and kept at this temperature for 1 hour.
[0023] Furthermore, in the step 1, a selective laser melting forming experiment is performed on IN718Plus alloy powder with the selective laser melting parameters of laser power 135W, scanning rate 900mm / s, layer thickness 0.02mm, and overlap spacing 0.08mm to obtain deposited IN718Plus alloy;
[0024] In the step 2, the deposited IN718Plus alloy sample is subjected to the first heat treatment at a furnace temperature of 1100° C. and kept at this temperature for 1.5 hours.
[0025] The present invention also provides an IN718Plus alloy obtained by being treated by the method for improving the high temperature performance of the selective laser melted IN718Plus alloy. The IN718Plus alloy is an IN718Plus alloy with a unipolar distribution of the γ' phase. The unipolar γ' phase is evenly distributed, has a size of 17 to 42 nm, and a content of about 28% to 32%. An appropriate amount of needle-shaped η phase is precipitated at the grain boundary.
[0026] Or the IN718Plus alloy is an IN718Plus alloy with a bipolar distribution of the γ' phase, that is, the size of the strengthening phase γ' in the alloy is graded, wherein the size of the large-sized γ' phase is 88 to 110 nm, and the content is about 4.4% to 6%; the size of the small-sized γ' phase is 11 to 37 nm, and the content is about 18.2% to 21.2%; and an appropriate amount of needle-shaped η phase is precipitated at the grain boundary.
[0027] The beneficial effects of the present invention are as follows: the present invention takes IN718Plus alloy as the research object, and prepares IN718Plus alloy by selective laser melting technology. The method of the present invention realizes the regulation of the unipolar and bipolar γ' phases of IN718Plus alloy by controlling the cooling mode after solid solution.
[0028] At the same time, the IN718Plus alloy with bipolar γ' phase was obtained by this method, which greatly improved the high-temperature stability of the γ' phase, thereby improving the high-temperature mechanical properties of the IN718Plus alloy, which is of great significance for the future production and use of the alloy. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a microstructural characterization diagram of the deposited structure of the present invention;
[0030] Figure 2 This is a microstructure characterization diagram of the sample after homogenization treatment of the present invention;
[0031] Figure 3 The microscopic characterization diagram of two heat-treated samples of the present invention, namely, WQ and AC samples;
[0032] Figure 4 The room temperature tensile performance diagram of the WQ specimen, AC specimen, and forging standard and actual measurement of the present invention;
[0033] Figure 5 This is a diagram of the high temperature tensile properties of the WQ and AC samples of the present invention at 704°C. DETAILED DESCRIPTION
[0034] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0035] In order to achieve the above object, the present invention provides the following specific implementation methods:
[0036] Example 1: Figures 1 to 5 As shown, a method for improving the high temperature performance of selective laser melted IN718Plus alloy includes the following steps:
[0037] Step 1: Prepare IN718Plus alloy specimens using selective laser melting:
[0038] On the selective laser melting platform of BLT S210, under the conditions of laser power of 85-185W, scanning rate of 300-1350mm / s, layer thickness of 0.02-0.03mm, and overlap spacing of 0.06-0.2mm, the selective laser melting forming experiment was carried out on the IN718Plus alloy powder prepared by gas atomization method, and the particle size of the powder was 15μm-45μm; thus, the deposited IN718Plus alloy sample was obtained, and the density of the deposited IN718Plus alloy sample was 8.236g / cm3, the relative density was 99.83%, and the columnar grain size in the sample was 5-50μm;
[0039] Step 2: Homogenization:
[0040] The deposited IN718Plus alloy sample is subjected to the first heat treatment at a furnace temperature of 1050-1150°C and a heat preservation period of 1-1.8h. After the treatment, it is water-cooled to room temperature at a rate of 1200-1400°C / s to obtain the IN718Plus alloy sample after homogenization. The grains in the IN718Plus alloy sample after homogenization are equiaxed grains with a grain size of 28-30μm.
[0041] Step 3: Solution treatment:
[0042] The IN718Plus alloy sample after homogenization was subjected to a second heat treatment at a furnace temperature of 960-980°C for 1-1.5 hours, and then water-cooled to room temperature at a rate of 1200-1400°C / s.
[0043] Step 4: Cooling and double aging treatment:
[0044] Under the condition of furnace temperature of 780-796°C, keep it warm for 8h-9h, then cool it to 696-712°C at a cooling rate of 56°C per minute, keep it warm for another 8h-9h, that is, complete the third heat treatment, and finally, air cool it to room temperature at a rate of 200-300°C / s;
[0045] That is, the high temperature performance improvement of the selective laser melted IN718Plus alloy is completed.
[0046] Example 2: The same as Example 1, except that in step 3, the IN718Plus alloy sample after homogenization is subjected to a second heat treatment at a furnace temperature of 960° C. and kept at this temperature for 1 h.
[0047] Example 3: The same as Example 1, except that: in step 1, a selective laser melting forming experiment is performed on IN718Plus alloy powder with a laser power of 135W, a scanning rate of 900mm / s, a layer thickness of 0.02mm, and an overlap spacing of 0.08mm to obtain a deposited IN718Plus alloy;
[0048] In step 2, the deposited IN718Plus alloy sample is subjected to the first heat treatment at a temperature of 1100° C. for 1.5 hours.
[0049] Due to the excellent high temperature mechanical properties and stability of IN718Plus alloy, it has a large market in many fields including the aerospace field. Traditional production methods have problems such as long production cycle and serious waste of resources. Therefore, this embodiment adopts the process parameters of laser power 135W, scanning rate 900mm / s, layer thickness 0.02mm, and overlap spacing 0.08mm to selectively laser melt IN718Plus alloy with high density and good metallurgical bonding. The density of the sample is 8.236g / cm3 and the relative density is 99.83%. Figure 1 The figure shows the microscopic characterization of the deposited sample. The sample is mainly composed of Laves phase and cellular substructure. The grain composition is coarse and uneven columnar grains along the deposition direction, and the grain size is 5 to 50 μm.
[0050] Due to the layer-by-layer stacking process of additive manufacturing, each deposited layer of the material has undergone extremely hot and cold processes, so the uniformity of the structure is very poor and it needs to be homogenized. The homogenization method selected in this example is to keep the temperature at 1100℃ for 1.5 hours and then cool it with water. The structure morphology of the sample after homogenization is as follows: Figure 2 As shown in the figure, the molten pool line and Laves phase of the homogenized sample have been completely dissolved, and the average grain size is 28μm. At this time, the recrystallization of the alloy has reached the level of complete recrystallization, and the grains have completely changed from columnar crystals to equiaxed crystals.
[0051] Example 4: The present invention also provides an IN718Plus alloy obtained after being treated by the method for improving the high temperature performance of the selective laser melted IN718Plus alloy provided in Examples 1 to 3, wherein the IN718Plus alloy is an IN718Plus alloy with a unipolar distribution of the γ' phase, the unipolar γ' phase is uniformly distributed, has a size of 17 to 42 nm, and a content of about 28% to 32%; an appropriate amount of needle-shaped η phase is precipitated at the grain boundary.
[0052] Example 5: The same as Example 1, except for the solution treatment in step 3, specifically: after the second heat treatment, air cooling to room temperature is performed at a rate of 200-300°C / s.
[0053] Example 6: The same as Example 5, except that the IN718Plus alloy sample after homogenization is subjected to a second heat treatment at a furnace temperature of 960° C. and kept at this temperature for 1 hour.
[0054] Example 7: The present invention also provides an IN718Plus alloy obtained by being treated with the method for improving the high temperature performance of the selective laser melted IN718Plus alloy provided in Examples 5 and 6, wherein the IN718Plus alloy is an IN718Plus alloy with a bipolar distribution of the γ' phase, i.e., the size of the strengthening phase γ' in the alloy is graded, wherein the size of the large-sized γ' phase is 88 to 110 nm, and the content is about 4.4% to 6%; the size of the small-sized γ' phase is 11 to 37 nm, and the content is about 18.2% to 21.2%; and an appropriate amount of needle-shaped η phase is precipitated at the grain boundary.
[0055] In order to further describe the present invention, the present invention provides the following experimental instructions: Figures 1 to 5 As shown,
[0056] like Figure 1 As shown in the figure, the deposited microstructure is mainly composed of matrix γ, Laves phase and cellular substructure. There are a large number of molten pool lines perpendicular to the deposition direction, and the grain morphology is coarse and uneven columnar grains. After homogenization treatment, the cellular substructure, Laves phase and molten pool boundary lines are completely dissolved, and the phase composition is only matrix γ phase.
[0057] like Figure 2 As shown in the figure, after homogenization treatment at 1100℃, the grain composition is fine and uniform equiaxed grains, and the size and orientation of the grains are close to those of forging materials. Therefore, after homogenization treatment, two groups of heat treatments were carried out, namely, the first group of heat treatment and the second group of heat treatment, and WQ and AC samples were obtained respectively.
[0058] like Figure 3 As shown in the figure, the microscopic characterization of the WQ sample revealed that a proper amount of needle-shaped η phase was precipitated at the grain boundary of the alloy; in addition, due to the double aging process, a large amount of γ' phase was precipitated in the alloy, and its size and distribution were relatively uniform, with a size of about 30nm. The cooling rate after solution treatment at 960℃ may affect the size and distribution of the precipitated phase.
[0059] like Figure 3 As shown, microscopic characterization of the AC sample revealed that needle-shaped η phase was also precipitated at the grain boundary; characterization of the main strengthening phase γ' phase revealed that the γ' phase in the AC sample showed a graded phenomenon, in which the large-sized γ' phase was about 93nm in size and the small-sized γ' phase was about 28nm in size.
[0060] It can be found that after double aging, a large amount of γ' phase was precipitated in both samples. The size and distribution of the γ' phase in the WQ sample were very uniform, but the γ' phase in the AC sample showed a graded phenomenon. This shows that the cooling rate after 960℃ is the key to whether the γ' phase is graded.
[0061] Then, the WQ and AC specimens were subjected to room temperature tensile tests and compared with the forgings. Figure 4 As shown, the room temperature tensile properties all exceed the forging standards, with a yield strength of 0.958 GPa, a tensile strength of 1.338 GPa, and an elongation of 15%.
[0062] Next, the WQ and AC samples were subjected to 704℃ high temperature tensile tests. The results are as follows: Figure 5 As shown in the figure, the experimental results show that the yield strength of the AC sample decreased by less than 2% compared with the room temperature tensile test. It can be seen that the high temperature stability of the γ' phase with bimodal distribution in the AC sample is higher than that of the uniformly distributed γ' phase in the WQ sample (strength decreased by 9.6%).
[0063] The heat treatment method for regulating the size distribution of the γ' phase of the selective laser melted IN718Plus alloy provided by the present invention can obtain a WQ sample with a unipolar distribution of the γ' phase and an AC sample with a bipolar distribution of the γ' phase by changing the cooling method after the 960°C solid solution. By comparing the room temperature tensile property test results of the two samples with the 704°C high temperature tensile property test results, it is obtained that the high temperature stability of the γ' phase with a bipolar distribution in the AC sample is higher than that of the unipolar distribution of the γ' phase in the WQ sample.
[0064] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for improving the high temperature performance of selective laser melted IN718Plus alloy, characterized in that: The steps include: Step 1: Prepare IN718Plus alloy specimens using selective laser melting: On the selective laser melting platform of BLT S210, the selective laser melting forming experiment was carried out on the IN718Plus alloy powder prepared by gas atomization method under the conditions of laser power 85-185W, scanning rate 300-1350mm / s, layer thickness 0.02-0.03mm, and overlap spacing 0.06-0.2mm to obtain the deposited IN718Plus alloy sample; Step 2: Homogenization: The deposited IN718Plus alloy sample is subjected to the first heat treatment at a furnace temperature of 1050-1150°C and a heat preservation period of 1-1.8h, and then water-cooled to room temperature at a rate of 1200-1400°C / s to obtain the homogenized IN718Plus alloy sample; Step 3: Solution treatment: The homogenized IN718Plus alloy sample was subjected to a second heat treatment at a furnace temperature of 960-980°C for 1-1.5 hours, and then water-cooled to room temperature at a rate of 1200-1400°C / s. Step 4: Cooling and double aging treatment: Under the condition of furnace temperature of 780-796°C, keep it warm for 8h-9h, then cool it to 696-712°C at a cooling rate of 56°C per minute, keep it warm for another 8h-9h, that is, complete the third heat treatment, and finally, air cool it to room temperature at a rate of 200-300°C / s; That is, the high temperature performance improvement of the selective laser melted IN718Plus alloy is completed.
2. The method for improving the high temperature performance of selective laser melted IN718Plus alloy according to claim 1, characterized in that: The step 3, solution treatment, is as follows: After the second heat treatment is completed, the material is air-cooled to room temperature at a rate of 200-300°C / s.
3. The method for improving the high temperature performance of selective laser melted IN718Plus alloy according to claim 1, characterized in that: The particle size of the IN718Plus alloy powder in step 1 is 15 μm to 45 μm.
4. The method for improving the high temperature performance of selective laser melted IN718Plus alloy according to claim 1, characterized in that: The density of the IN718Plus alloy sample described in step 1 is 8.236 g / cm3, the relative density is 99.83%, and the columnar grain size in the IN718Plus alloy sample is 5 to 50 μm.
5. The method for improving the high temperature performance of selective laser melted IN718Plus alloy according to claim 1, characterized in that: The grains in the IN718Plus alloy sample after the homogenization treatment in step 2 are equiaxed grains, and the grain size is 28 to 30 μm.
6. The method for improving the high temperature performance of selective laser melted IN718Plus alloy according to claim 1, characterized in that: In the step 3, the IN718Plus alloy sample after homogenization is subjected to a second heat treatment at a furnace temperature of 960° C. and kept at this temperature for 1 hour.
7. The method for improving the high temperature performance of selective laser melted IN718Plus alloy according to claim 2, characterized in that: The IN718Plus alloy sample after the homogenization treatment was subjected to a second heat treatment at a furnace temperature of 960° C. and kept at this temperature for 1 hour.
8. The method for improving the high temperature performance of selective laser melted IN718Plus alloy according to any one of claims 1 to 7, characterized in that: In the step 1, a selective laser melting forming experiment is performed on IN718Plus alloy powder with the selective laser melting parameters of 135W laser power, 900mm / s scanning rate, 0.02mm layer thickness, and 0.08mm overlap spacing to obtain deposited IN718Plus alloy; In the step 2, the deposited IN718Plus alloy sample is subjected to the first heat treatment at a furnace temperature of 1100° C. and kept at this temperature for 1.5 hours.
9. The IN718Plus alloy obtained by the method for improving the high temperature performance of the selective laser melted IN718Plus alloy as claimed in claim 1 or 3 or 4 or 5 or 6 or 7 or 8 is characterized in that: The IN718Plus alloy is an IN718Plus alloy with γ' phase unipolar distribution, the unipolar γ' phase is evenly distributed, the size is 17-42nm, and the content is about 28%-32%; a proper amount of needle-shaped η phase is precipitated at the grain boundary.
10. The IN718Plus alloy obtained by the method for improving the high temperature performance of the selective laser melted IN718Plus alloy according to any one of claims 2 to 8 is characterized in that: The IN718Plus alloy is an IN718Plus alloy with a bipolar distribution of the γ' phase, that is, the size of the strengthening phase γ' in the alloy is graded, wherein the size of the large-sized γ' phase is 88 to 110 nm, and the content is about 4.4% to 6%; the size of the small-sized γ' phase is 11 to 37 nm, and the content is about 18.2% to 21.2%; and an appropriate amount of needle-shaped η phase is precipitated at the grain boundary.
Citation Information
Patent Citations
Method of heat treating a ni-based superalloy article and article made thereby
CN102021508A
Composite additive manufacturing method of large-size In718 high-temperature alloy components
CN111001808A
Selective laser melting forming Inconel718 alloy and heat treatment method thereof
CN111360266A
Preparation method of high-strength and high-plasticity Inconel718 alloy based on SLM
CN113477942A
Heat treatment method for ultrahigh-plasticity Inconel 718 alloy prepared based on SLM
CN114752873A